2023
DOI: 10.1111/mec.16912
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in functional traits and interactions patterns of soil methane‐cycling communities following forest‐to‐pasture conversion in the Amazon Basin

Abstract: Deforestation threatens the integrity of the Amazon biome and the ecosystem services it provides, including greenhouse gas mitigation. Forest-to-pasture conversion has been shown to alter the flux of methane gas (CH4) in Amazonian soils, driving a switch from acting as a sink to a source of atmospheric CH4. This study aimed to better understand this phenomenon by investigating soil microbial metagenomes, focusing on the taxonomic and functional structure of methane-cycling communities. Metagenomic data from fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 143 publications
(218 reference statements)
0
3
0
Order By: Relevance
“…The network properties (i.e., eigenvector centrality, number of modules, clustering coefficient, degree, and edges) were evaluated to detect differences in the topology and strength of the networks. In particular, eigenvector centrality was used in combination with the centre log ratio as described in Obregon Alvarez et al (2023) to select hub taxa or keystone taxa in both the organic and mineral soils. Network metrics and visualization were performed in Gephi (version 0.9.2) (Bastian et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The network properties (i.e., eigenvector centrality, number of modules, clustering coefficient, degree, and edges) were evaluated to detect differences in the topology and strength of the networks. In particular, eigenvector centrality was used in combination with the centre log ratio as described in Obregon Alvarez et al (2023) to select hub taxa or keystone taxa in both the organic and mineral soils. Network metrics and visualization were performed in Gephi (version 0.9.2) (Bastian et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…However, the nature and extent of these influences may be driven by an intricate interplay of environmental factors [ 30 , 69 , 72 ]. Several studies have investigated the role of CH 4 -related microbial communities in Amazonian floodplains and upland soils [ 2 , 5 , 25 , 57 , 82 ]. For instance, Venturini et al [ 82 ] found that an increase in soil moisture led to changes in the CH 4 -related microbial communities and increased CH 4 emissions in Amazonian soils.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have primarily investigated the cooccurrence patterns of either methanogens (Zhang, Jiao, et al, 2018) or methanotrophs (Ho et al, 2016), respectively, rarely as a combined network. Li, Hambright, et al (2021) had studied the interactions between methanogens and methanotrophs in the lake system, and Alvarez et al (2023) focused on the land use change effects on methane-cycling microbes in forest-to-pasture ecosystems. Although there have been discussions on the co-occurrence links between these two groups among environmental gradients (Obregon et al, 2023) and seasonal changes (Wang et al, 2022) in agriculture systems and also in rice fields (Wang et al, 2023), there has not been a concerted effort to explore the spatial disparities of linkage among soil compartments between the methanogen and methanotroph communities in paddy fields and how this linkage varies along environmental gradients.…”
mentioning
confidence: 99%